Design and realisation of radio‐frequency attenuators based on microelectromechanical system switches. (1st November 2016) - Nan, Xueli; Zhang, Binzhen; Yang, Xin; Ge, Shaolei
Abstract : Radio‐frequency (RF) attenuators show unique advantages and a great development potential in phased array radars. A kind of programmable step attenuators with high precision based on contact‐type microelectromechanical system series switches is proposed herein. This work paid attention to the design and fabrication of switches – the key components of attenuators. By setting up vent holes on the pull‐down plates of switches, the mass of plates was reduced, together with the decreased influence of air damping. Meanwhile, switches were manufactured and packaged through ultraviolet lithography (UV‐LIGA) technology with the S parameter test being performed. Results showed that the insertion loss in a range of 0.3 and 1.8 dB under the condition that attenuation modules are short‐circuited at the same time, which is basically the same with the simulation results of 0.1–1.3 dB. While all the return losses S 11 were <15 dB expect from that at 10 dB. In addition, the designed attenuator showed gentle attenuation in a range of DC ∼20 GHz. However, on the whole, the deviation is controlled within 2 dB, which is basically consistent with the design results of 1 dB. It can be found from the obtained results that all indices of the attenuator satisfied the design requirements.